Role of Mango in the Production of Wine: A Review - Mohd Kamran; Kokab Askari; Bhavya Trivedi; Rupak Nagraik; Mohammad Faisal; Aditi Nayek; Gorantla Leeladhar; Aryan Singh; Shivam; Thrunshi Hiloto; Rohit Joshi (Malaysian Journal of Science, 2025)
Mango is considered to be one of the most cultivated tropical fruits around the world. India is one of the largest producers of mango, accounting for an estimated 45% of the total world mango fruit production. India exported 27,872 metric tons of mango, worth 327.45 crores in 2020-21. Mango is a perishable fruit with a very short shelf life, which leads to wastage. To minimize or utilize the wastage, alternative mango-based products are being produced. Mango wine is one of the alternatives for surplus mango production. It is cost-effective and helps minimize post-harvest losses. The Philippines is the largest manufacturer of mango-based alcoholic beverages, such as mango wine and rum. Locally, mango wine is a popular home-based alcoholic beverage in the Philippines. India and Kenya are also experiencing significant growth in fruit wine production. The available literature on the production and characterization of mango wine briefly describes the fermentation and characterization procedures followed. The physiochemical properties and volatile composition of mango wine, including ethanol, esters, total soluble solids, and sensory analysis, are also highlighted in the review. The study provides evidence that the antioxidants and immunoboosters can reduce the risk of chronic infections.